Outcome of primary ventral hernia repair with monofilament polyester composite ventral patch in a community-based hospital - Kumar R., Hareesh; Arulraj Solomon, Alfred; Veeraraghavan, Rajakumar (International Surgery Journal, 2024)
Background: Ventral hernia repair (VHR) is one of the common surgical procedures carried out in general surgery. This study assessed the post operative outcomes in patients with primary ventral hernia undergoing repair using monofilament polyester composite ventral patch Parietex™ Covidien (PCO-VP). Methods: A prospective single proportion observational study of 54 patients undergoing open VHR for primary ventral hernia with the PCO-VP in a community-based hospital was carried out. The patients were followed up for a period of one year from day of surgery. Primary outcome was recurrence, and secondary outcomes were reoperations and complications including seroma, hematomas, abdominal wall abscess, wound infections, and mesh infections. Results: Our sample size of (n=54) included 35 (65%) females and 19 (35%) males with a mean hernia defect diameter of 3.5±0.4 cm. 83% (45) underwent elective surgery (EL) and 17% (9) underwent emergency surgery with a mean operative time of 98.5 minutes, 11% (n=6) patients needed alteration of the technique and 20% (n=11) patients needed mesh repositioning, 12 adverse events were noted during the hospital stay. No mesh infections, early recurrences, readmissions or revision surgeries were noted. Patients had a average Carolina comfort scale score of 4/115 noted at the end of study. Conclusions: The use of PCO-VP to repair primary ventral hernia yielded nearly nil early recurrence rate, low postoperative complications and high satisfaction ratings, PCO-VP repair is a highly effective method for small and moderate size ventral hernias in both elective and emergency setting.